(untitled) (Journal Of Educational and Psychological Researches, 2023)
The aim of the research is to measure the change in the impact of the factors of the Corona pandemic on psychological sensitivity and COVID-19 phobia in a sample of Bisha University students and to detect the differences in the phobia (phobia) Covid-19 among the sample members in the measurement before the ban and after the ban was opened, in addition to the differences in psychological sensitivity of The sample has between sizes before and after the spread of the Corona pandemic, as well as the differences in them according to the gender variable (male, female). The researcher relied on the comparative approach. The scale of psychological sensitivity and COVID-19 phobia was applied to a sample of (62) male and female respondents. The results revealed significant differences in COVID-19 pre-post-phobia in favor of post-measurement, there are no differences found between pre-post- in reactive and emotional sensitivity. In addition, there are no significant differences in these dimensions regarding gender.